Antecedents of Organisational Commitment Among Employees in Malaysia Public Service Department - Jaye, Kendaka Baboucarr (1999)
Serv ice Department's (MPSD) employees, spec ifically their levels of affect ive states, job sat isfact ion, turnover intention, and organisational commitment. It analyses the extent to wh ich affect ive states, job sat isfact ion, and turnover intent ion var iables are s ign ificant to organisat ional commitment relat ionsh ip. Spec ifically, it undertook to determ ine how employees' perceptions of the organ isat ion's prospects and the ir percept ions of the ir own career opportunit ies m ight affect comm itment d imens ions, for example, loyalty, and involvement. Spec ifically, the objectives of the study are to determine : a) the level of organ isat ional comm itment among employees of publ ic serv ice, b) the d ifferences among d ifferent level of attitudes in the publ ic service w ith regards to organisat ional comm itment, affect ive states, job sat isfact ion, and turnover intent ion, c) the relat ionsh ip of affect ive states, job sat isfact ion, and turnover intent ion w ith organisational commitment,d) the relationship between demographic characteristics and organisational commitment of employees. Hypothesised relationships were tested using structured survey responses from the public service employees. Reliability, frequencies, Pearson's Product Moment correlation were used to analyse the data. A survey, using self-administered questionnaires was conducted on respondents of200 of the total population accessible employees ofMPSD and 58% responded. Job Descriptive Index (Smith, Kendall, and Hulin, 1 969) was used to measure job satisfaction, while Organisational Commitment Questionnaire (Mowday and Steers, 1 979) was used to measure organisational commitment. Affective states inventory (French, Chaplan, and Harrison, 1 984) was used to measure affectivity, while instrument using four-item adapted from Hunt, Osborn, and Martin ( 198 1 ) was used to measure turnover intention. Major findings of the study revealed that: 1 ) Majority of the respondents (63.8%) appeared to be moderately committed to the organisation. 2) Majority of the respondents (69%) appeared to be moderately satisfied and for intention to stay, employees were moderate (50%) to low (44%). 3 ) The correlation between demographic variables (such as age, sex, and marital status, tenure, and income) and organisational commitment show an indication of positive relationship. 4) The correlation of job satisfaction, affective states and turnover intention to organisational commitment show a weak correlation since the (r < 0.5), but despite the weaknesses, it indicates a positive relationship.